2018
DOI: 10.1097/md.0000000000013577
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of Injinoryung-San-Gagambang (Yinchen Wuling powder) decoction on stroke patients with elevated serum liver enzymes

Abstract: Rationale:Injinoryung-San-Gagambang (IJORS) effectively improves hepatic dysfunction caused by polypharmacy in stroke patients.Patient concerns:We present 3 cases of hepatic dysfunction caused by polypharmacy, one of which was a 51-year-old man with cerebellum infarction and pneumonia as a complication of stroke. He took multiple medications because of baseline diseases. After recurrence of pneumonia, his laboratory tests showed abnormal aminotransferase levels. Another patient was an 81-year-old woman with ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, the reliability of these cases is not expected to be low, since a clear improvement of abnormal ATLs after herbal medicine treatment has been confirmed, and these cases are consistent with the results of the previous studies. 10,24) Despite these limitations, this study suggests the possibility of applying HMA to liver disease. If larger scale and prospective method studies conducted on the same topic in the future, it will (427) lead to more specific and clearer conclusions about the potential power of herbal medicine`s use of hepatic disease.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, the reliability of these cases is not expected to be low, since a clear improvement of abnormal ATLs after herbal medicine treatment has been confirmed, and these cases are consistent with the results of the previous studies. 10,24) Despite these limitations, this study suggests the possibility of applying HMA to liver disease. If larger scale and prospective method studies conducted on the same topic in the future, it will (427) lead to more specific and clearer conclusions about the potential power of herbal medicine`s use of hepatic disease.…”
Section: Discussionmentioning
confidence: 88%
“…7,8,9) Furthermore, we have also reported some cases with improved ATLs after herbal medicine administration. 10,11) These mean that herbal medicine can be safe intervention and have therapeutic effect for liver dysfunction as long as it is prescribed properly. 12) In our previous study, we only reported the cases of Injin-Oryongsan single decoction treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical study observed that it can slightly improve hepatic dysfunction in stroke patients. 6 In this study, we investigated the efficacy and safety of Wu-Ling San and Yin Chen Wu-Ling San in patients with gout through a double-blinded, placebo-controlled clinical trial to clarify the potential clinical benefit of these TCM in patients with gout.…”
Section: Yin Chen Wu-ling Sanmentioning
confidence: 99%
“…This formulation is recommended for conditions such as jaundice, oliguria, hyperlipidemia, and a fatty liver. A clinical study observed that it can slightly improve hepatic dysfunction in stroke patients 6 …”
Section: Introductionmentioning
confidence: 99%